Deep SORT Related Studies - Majid, Abdul; Qinbo, Qinbo; Saba Brahmani (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Computer vision is the field of computer science in which computers are made capable to see and recognize like human being. Deep learning is using multiple layers for the purpose of understanding and recognizing various objects. Deep Simple Real Time Tracker is the area in which the objects are tracked in real time from multiple images and videos. Many researchers have contributed to the field and various algorithms have been proposed. The current study presents the deep SORT related studies in which the various algorithms have been presented for the sake of understanding and starting point for the researchers interested in computer vision and deep sorting. The single shot detection, feature extraction, have been explained along with the research conducted. Feature selection and extraction, matching recognition, object tracking through frames have been appended to the current study.